Analysis of E-LKPD Development Needs on Fraction Materials Using the Pmri Approach for Students of SDN 4 Air Balui Musi Banyuasin - Eko Windarti; Somakim Somakim; Erna Retna Safitri (Green Publisher Indonesia, 2025)
Study This aim For analyze need development of E-LKPD based on PMRI on material fractions For students of SDN 4 Air Balui , Musi Banyuasin . The research method used is Research and Development (R&D) with the ADDIE development model ( Analysis, Design, Development, Implementation, Evaluation ). At this stage analysis needs , data collected through questionnaires distributed to students and teachers. Analysis results show that student own need tall towards digital- based E-LKPD which is interesting , contextual and supportive understanding draft fractions . As many as 59% of students strongly agree with relatedness draft with life daily , and 41% of students agree . Need towards digital learning media reached 49% strongly agree and 48% agree . This aspect clarity and ease presentation material assessed important by 55% of students who strongly agree and 45% who agree . For educators , PMRI -based E-LKPD is expected can help student understand draft fractions through experience real and improving skills think creative mathematical they. Findings This underline importance development of PMRI -based E-LKPD as a valid, practical and effective learning medium.